1988
DOI: 10.1073/pnas.85.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bonds and thermal stability in T4 lysozyme.

Abstract: Disulfide bonds are thought to serve a stabilizing role in extracellular globular proteins, but little is known about the modes of stabilization or their mechanisms. Thermodynamic data presented here demonstrate that an engineered 3-97 disulfide bond previously shown to stabilize T4 lysozyme in vitro against irreversible thermal inactivation also stabilizes the molecule against reversible thermal unfolding. In this paper, we explore the relationship between the disulfide's thermodynamic contribution to protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 42 publications
6
92
2
Order By: Relevance
“…In addition, AH, for these variants is greatly reduced, indicating that the presence of these crosslinks destabilizes the protein (Wetzel et al, 1988). Three other novel disulfides increase T, by 5-10 "C (Matsumura et al, 1989a,b) at low pH, and combinations of these crosslinks are nearly additive in their ability to increase T,,, (Matsumura et al, 1989b), although the tendency of these crosslinks to increase resistance to denaturation at neutral pH (Wetzel et al, 1988) or under low-temperature denaturing conditions (Anderson et al, 1990) is diminished. However, each of these "stabilizing" crosslinks raises AC, and lowers AH, (Matsumura et al, 1989a).…”
Section: Novel Disulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AH, for these variants is greatly reduced, indicating that the presence of these crosslinks destabilizes the protein (Wetzel et al, 1988). Three other novel disulfides increase T, by 5-10 "C (Matsumura et al, 1989a,b) at low pH, and combinations of these crosslinks are nearly additive in their ability to increase T,,, (Matsumura et al, 1989b), although the tendency of these crosslinks to increase resistance to denaturation at neutral pH (Wetzel et al, 1988) or under low-temperature denaturing conditions (Anderson et al, 1990) is diminished. However, each of these "stabilizing" crosslinks raises AC, and lowers AH, (Matsumura et al, 1989a).…”
Section: Novel Disulfidesmentioning
confidence: 99%
“…Of these, the most extensively studied is T4 lysozyme, which has no disulfides in its native form. Five different novel disulfide bonds have been introduced into this protein (Perry & Wetzel, 1984;Wetzel et al, 1988;Matsumura et al, 1989a,b). Two have been found to lower T,,, by 20 "C at neutral pH.…”
Section: Novel Disulfidesmentioning
confidence: 99%
“…Recombinant DNA technology has allowed the construction of proteins of altered stability in vitro (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), catalytic efficiency (17)(18)(19), substrate specificity (20)(21)(22)(23), and resistance to in vivo thermal inactivation (24) through the use of single or multiple amino acid substitutions. This effort has been greatly helped by the fact that the effects of amino acid substitutions on such properties of proteins tend to be additive as mutations accumulate, provided that the substituting residues do not interact functionally or by direct contact (25).…”
mentioning
confidence: 99%
“…When the enzyme was heated at 75 "C for 30 min at neutral pH, however, these cysteines were oxidized to cystine without affecting the catalytic activity of TBADH. As the results of many studies have suggested that disulfide bonds confer rigidity and stability on certain proteins (Nakamura et al, 1978;Wetzel et al, 1988;Matsumura et al, 1989;Dohlman et al, 1990;Mely & Gerard, 1990;Kanaya et al, 1991), several investigators have attempted to introduce disulfides to enhance the thermal stability of proteins, using such methods as site-directed mutagenesis (Wetzel et al, 1988;Matsumura et al, 1989;Luckey et al, 1991) or grafting cysteine-containing peptides (Magonet et al, 1992), for example. To probe the function of the cystine 283-295 disulfide in TBADH, we used site-directed mutagenesis to replace cys 283 with serine.…”
Section: Discussionmentioning
confidence: 99%